The Multiband Emission of the Two-component Gamma-Ray Burst Jet Influenced by Progenitor Winds within the Accretion Disk of Active Galactic Nuclei - Hao-Yu Yuan; Wei-Hua Lei (The Astrophysical Journal, 2025)
Gamma-ray bursts (GRBs), both from the merger of binary compact objects (short GRBs) and the collapse of massive stars (long GRBs), are expected to occur in dense environments, e.g., the accretion disks of active galactic nuclei (AGNs). The propagating of GRB jets in such dense environments will result in multiband transients. Investigating the properties of these transients plays an important role in their identification, understanding the jet structure, and constraining the population of the star and compact objects in AGNs disks. In this work, we study the propagation and emission of a two-component GRB jet (a fast narrow component and a wide slow one) in an AGN disk. We consider the influence of wind from short and long GRB progenitors, which reconstruct the surrounding density distribution and form a cavity in the AGN disk. We find that long GRB jets are choked, and the dynamics and emission resemble the case without a cavity. The cocoon breakout emission can be detected by Einstein Probe (EP) and Hard X-ray Modulation Telescope (HXMT). For short GRBs, we expect a nonthermal afterglow emission from the narrow and wide jet (if it is more energetic than the narrow one) and a cocoon breakout emission from the choked wide jet, which can be monitored by EP and HXMT, respectively. Therefore, joint observations by EP and HXMT might be helpful to distinguish the types of GRBs in AGNs disks and the jet components.